DISKURSUS HEGEMONI PASCAKOLONIAL DALAM EUROPEAN GREEN DEAL & PELARANGAN MINYAK SAWIT INDONESIA - Megatari Pasang, Nur Aprilia; Kuswardini, Seftina (Universitas Jenderal Ahmad Yani, 2025)
This thesis examines how the sustainability discourse in the European Green Deal (EGD) and Renewable Energy Directive II (RED II) policies reproduce postcolonial relations of domination in the palm oil trade between the European Union and Indonesia. Using a postcolonial approach, especially Edward Said’s thougths on orientalism, shows that the sustainability narrative built by the European Union is not neutral, but a hegemonic narrative with internal economic interests that strengthen the position of the West / Global North over East / Global South. Through discourse analysis of the EGD and RED II, it is found that the EU frames palm oil as a high-risk commodity by ignoring the social reality of producer countries. This indicates a hidden discriminatory practice in the sustainability discourse. This finding confirms that there is an active discourse in the EGD, which perpetuates global inequality, and strengthens the relations of domination between the European Union and Indonesia in the postcolonial era.